Keteladanan Orang Tua Dalam Proses Pembelajaran Tahfidz Siswa Kelas 6 di SDIT Darul Hijri Dramaga Bogor - Wapi Rukmawati; Sutisna sutisna; Oking Setia Priyatna (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The family is the environment where the child finds education firstly. Therefore, the role of parents in education is a direct action to supervise, control, and evaluate every child's activity. In order for children's education to be better, parents must act as educators who can set an example or model for their children. This study aims to find out how important parental exemplary is in supporting school programs, especially in the Tahfidz learning process for grade 6 SDIT Darul Hijri Dramaga Bogor. This research is a field research using qualitative methods. Sources of data used are primary and secondary data obtained using techniques such as observation, interviews, and documentation. The results of the research and discussion show that parental example is very important and there are even parents who take part in the Al-Quran program to follow and be able to control their children's memorization at home. There are even children who are able to achieve the target of memorizing one juz or more, in general, children of students who have high motivation and most importantly, these children are children who are assisted, guided by their parents at home. However, this is not shown by all children who are students at SDIT Darul Hijri Dramaga Bogor because of the lack of ability and understanding of parents towards the Al-Quran, and parents are busy at work. Keywords: Exemplary, Parents, Tahfizh Learning